Modeling the influence of diffusion perturbations on the development of infectious diseases taking the convection and immunotherapy into account - Baranovskii, S.V.; Bomba, A.Ya.; Lyashko, S.I. (Reports of the National Academy of Sciences of Ukraine, 2021)
The mathematical model of the infectious disease is modified to account for the influence of diffusion perturbations and the convection on the dynamics of the immune response under immunotherapy. The solution of the corresponding singularly perturbed problem with time-delay is reduced to a sequence of solutions of problems without time-delay. Sought functions are represented in the form of asymptotic series as perturbations of solutions to the corresponding degenerate problems. We present the results of a numerical modeling that illustrate the influence of the diffusion redistribution of active factors on the infectious disease development under the immunotherapy conditions. The results demonstrate a decrease in the maximum concentration level of antigens in the locus of infection as a result of their diffusion redistribution.